Kid's slips : what young children's slips of the tongue reveal about language development - Jaeger, Jeri J. (NetLibrary., 2005)
The study of speech errors, or ""slips of the tongue,"" is a time-honored methodology which serves as a window to the representation and processing of language and has proven to be the most reliable source of data for building theories of speech production planning. However, until Kids' Slips, there has never been a corpus of such errors from children with which to work. This is the first developmental linguistics research volume to document how online processing is revealed in young children, ages 18 months through 5 years, through their slips of the tongue. Thus, this text provides a.